Survey of ICT and Education in Africa : Somalia Country Report - Hare, Harry (World Bank, Washington, DC, 2012)
This short country report, a result of larger Information for Development Program (infoDev) - supported survey of the Information and Communication Technologies (ICT) in education in Africa, provides a general overview of current activities and issues related to ICT use in education in the country. Somalia gained its independence in 1960, and 10 years later the country was plagued by a civil war that lasted for 21 years. By 1991, this war had ceased, but the education system had disintegrated beyond repair. Sporadic fighting among warlords guarding territorial interest continued until 2004 when the Transitional Federal Government (TFG) was installed to normalize the administration and bring back law and order. The country is still facing political challenges. In June 2006, a loose coalition of clerics, business leaders, and Islamic court militias, known as the Supreme Council of Islamic Courts (SCIC), defeated powerful Mogadishu warlords and took control of the capital. The courts continued to expand, spreading their influence throughout much of southern Somalia and threatening to overthrow the TFG. The education sector is greatly affected by this political instability which has resulted in the displacement of people, destruction of infrastructure and schools, and looting of equipment and books. As much as things are slowly returning to normal, thanks to the efforts of United Nations (UN) bodies, Non-governmental Organizations (NGOs), and local communities, education system revival and reforms are just but beginning. And as much as ICT is acknowledged as a possible tool in the reform agenda and a possible catalyst to bring about better quality and more accessible education in Somalia, it does not feature in the current plans of most of the organization working in Somalia or the ministry in charge.